Effect of adding concentrated myofibrillar proteins of silver carp (Hypophthalmichthys molitrix) on the qualitative and nutritional characteristics of pasta - Mahsa Karami Charvadeh; Eshagh Zakipour Rahimabadi; Parva Safari (تغذیه آبزیان)
Introduction: Pasta is a traditional grain-based food product that is popular worldwide. Wheat protein lacks some essential amino acids, which should be provided from the other sources to meet consumers' needs. Furthermore, most nutrients, such as essential amino acids, minerals, and vitamins, are removed from wheat grains during flour processing. In this study, concentrated myofibrillar proteins of silver carp, Hypophthalmichthys molitrix were used to increase the product protein and improve the amino acid profile of pasta. Materials and methods: This study was carried out to examine the effect of adding concentrated myofibrillar proteins of silver carp on the qualitative and nutritional characteristics of pasta. Research treatments included a control group and 5, 10, and 15% concentrated myofibrillar proteins (T5%, T10% and T15%, respectively). Some parameters such as amino acids, crude protein, fat, ash, moisture, pH, sensory analysis, as well as the quality characteristics of cooking, including cooking time, water absorption (%), and puffiness index, were measured. Results: The results showed a significant increase (p<0.05) in total amino acid content in treated samples compared to control. In addition, a significant elevation in the essential amino acids was observed in the treated samples. In the pre-cooking parameters, the percentage of protein (24.48%), fat (6.73%), ash (1.09%), and energy (398.41 kcal) upraised after adding the myofibrillar proteins to pasta, while the carbohydrate (59.96%), humidity (7.73%) and pH (6.71) were dropped. After the cooking process, protein, ash content, and pH increased. Instead, fat, carbohydrate, energy, and moisture content decreased. In the case of cooking parameters, cooking time (19.00 minutes) decreased by an elevation in the  myofibrillar protein. In contrast, other quality indices such as cooking loss (2.47 ± 0.06), water absorption percentage (124.42 ± 0.08%), and windiness index (4.83 ± 0.03) exhibited an increasing trend. The sensory analysis results showed that in terms of overall acceptability, no significant difference was observed between the control and T5% and T10%, while only  T15% was different from the others. Discussion: Based on the obtained results, adding concentrated myofibrillar protein of silver carp increased the protein content of pasta and changed the profile of amino acids, elevating the content of amino acids, essential and non-essential amino acids in the pasta product, exhibiting a positive effect of enriched pasta by adding concentrated myofibrillar protein of silver carp. On the contrary, the cooking time was reduced, possibly related to the elevated  protein content and the decreased carbohydrates in the formulated products. In addition, the swelling index showed an increasing trend, displaying the effect of concentrated myofibrillar protein on the elevated water absorption rate and water retention capacity during the cooking processes. Conclusion: Given the results of sensory analysis with chemical characteristics and quality characteristics of cooking the pasta, it can be concluded that enrichment with up to 10% concentrated myofibrillar fish proteins makes no difference compared to the control group, while enhancing the desired characteristics of the final product.